Concept Analysis of Pulmonary Rehabilitation - Dilla Fitri Ayu Lestari; Suhartini Ismail; Meira Erawati (Alta Dharma Publisher, 2020)
Pulmonary rehabilitation is a process of multi-disciplinary and comprehensive evidence-based for patients with chronic respiratory disease who are symptomatic and decreased daily of living activities. There is some literature discusses about pulmonary rehabilitation, but no one has analyzed the concept of pulmonary rehabilitation, particularly in the field of nursing. The concept of this analysis aims to analyze the concept of pulmonary rehabilitation by using Walker and Avant's concept analysis framework. There are some attributes influence pulmonary rehabilitation, such as the patient's condition, disease severity, and the environment that supports pulmonary rehabilitation. Antecedents concerning pulmonary rehabilitation include a history of past illnesses and the patient's lifestyle. The consequence towards pulmonary rehabilitation can be seen in two aspects, namely the patient and the health care system. Therefore, the pulmonary rehabilitation conceptual model should be based on attributes and antecedents to improve the quality of life of patients and quality of nursing services.